THE EFFECTS OF ALCOHOL-BASED ANTISEPTIC SOLUTIONS AGAINST STAPHYLOCOCCUS AUREUS AND STREPTOCOCCUS PYOGENES - Suyono, Handi; Wihanto, Laura (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction : Staphylococcus aureus and Streptococcus pyogenes are gram positive bacteria which can cause various diseases. The use of antiseptics is an effort that can be done in order to break the chain of transmission and reduce morbidity due to infection by microorganism. Alcohol as the main ingredients of antiseptics is probably the oldest and most widely used in various antiseptic products on the market. Despite their easy and practical use, reports of incidents of resistance to alcohol-based antiseptic agents to bacteria have been reported from several studies. Aim: Determine the inhibition of alcohol-based antiseptic solutions against Staphylococcus aureus and Streptococcus pyogenes bacteria. Methods : Kirby-Bauer disc-diffusion assays as susceptibility test. Zone of inhibition of growth diameter was performed in mm, with criteria resistance if ≤ 6 mm and sensitive if > 6 mm. We used 4 solutions namely A) ethanol 70%, B) ethanol 70% + H2O2 0,15%, C) ethanol 80%, D) ethanol 80% + H2O2 0,15%. Result : The assay results on Staphylococcus aureus showed the zone of inhibition of growth for solution ethanol 70%, ethanol 70% + H2O2 0,15%, ethanol 80%, and ethanol 80% + H2O2 0,15% are less than 6 mm which indicated that the antiseptic solution do not inhibit bacterial growth, as well as for all solutions against Streptococcus pyogenes. Different results were obtained from solution D (ethanol 80% + H2O2 0.15%) on S. aureus which indicate the zone diameter is 21 mm and classified having the ability to inhibit bacterial growth (sensitive). Conclusion: Exposure of gram positive bacteria, Staphylococcus aureus and Streptococcus pyogenes to clinically relevant concentrations of ethanol based antiseptic with or without hydrogen peroxide addition is not effective in inhibiting bacteria. Only an 80% alcohol-based antiseptic solution with the addition of H2O2 is still effective in inhibiting S. aureus . Further research needs to be done to review the recommended antiseptic formula and the need to add other ingredients to make an effective antiseptic in order to prevent infection.